1996
DOI: 10.1136/bmj.313.7062.919
|View full text |Cite
|
Sign up to set email alerts
|

Postal questionnaire study of disability in the community associated with psoriasis

Abstract: Objective-To study the disability caused by psoriasis in patients recorded as having psoriasis by their general practitioner.Design-Postal questionnaire survey using the psoriasis disability index and SF-36.Setting-Five general practices in Cleveland. Subjects-Of 767 patients identified, 546 completed the questionnaire and 435 were eligible and gave informed consent.Main outcome measures-Scores on SF-36 and psoriasis disability index.Results-The psoriasis disability index score was highly negatively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 17 publications
6
68
1
1
Order By: Relevance
“…12 UK researchers used the SF-36 and the Psoriasis Disability Index to demonstrate an inverse association between social class and degree of disability. 25 However, a US study of 87 patients at a tertiary medical clinic, in which three QoL instruments were assessed, found no relationship between HRQoL and any demographic variable, including age, gender and education. 26 The economic impact of psoriasis in terms of outof-pocket expenses increases with severity 27 and the effect is greater in lower income groups.…”
Section: Significance In Terms Of Ill-healthmentioning
confidence: 99%
“…12 UK researchers used the SF-36 and the Psoriasis Disability Index to demonstrate an inverse association between social class and degree of disability. 25 However, a US study of 87 patients at a tertiary medical clinic, in which three QoL instruments were assessed, found no relationship between HRQoL and any demographic variable, including age, gender and education. 26 The economic impact of psoriasis in terms of outof-pocket expenses increases with severity 27 and the effect is greater in lower income groups.…”
Section: Significance In Terms Of Ill-healthmentioning
confidence: 99%
“…Some studies showed that clinical severity and duration of psoriasis were not associated with any indices of quality of life, and that the form of stress contributes significantly more to the variance in patients' disability in everyday life than any other variable in medical or health status [4]. A recent survey of disability in patients with psoriasis showed a strong association between subjective disability and self-assessment of physical and mental well-being [9]. The basic research goal in this study was to determine the relationship between stressful life events and the appearance and course of psoriasis under the extreme conditions of war.…”
Section: Introductionmentioning
confidence: 99%
“…There is also good evidence to demonstrate that uk PCRNs focused on developing a research culture and a broad range of research including clinical research, social research, organizational research and research into complex interventions (Hay et al 1999;Lattimer et al 1998;O'Neill and kelly 1996;Bradley et al 1999;jolly et al 1999;Rait et al 2002). A key advantage of the regional PCRNs was that they seem to be able to sustain "large scale collaborative projects and small scale personally developed projects at the same time" (Thomas and While 2001).…”
Section: Primary Care Research Network In the United Kingdommentioning
confidence: 99%